Age Classification of the Existing Digital Game Content Rating System Across the World: A Comparative Analysis - Hamid, Ros Syammimi; Shiratuddin, Norshuhada (2018)
The negative effects of playing digital game with harmful content demonstrate that children indeed need to be protected. Thus, many countries implemented digital game content rating system with age classification to prevent the youngsters from playing age-inappropriate games which might be harmful to them. Although their ratings is claimed to be based on child development theories, however, it is found that different countries introduced different age classification. Unfortunately, Malaysia does not have its own digital game content rating system. Therefore, the purpose of this study is to analyse the current age classification in the existing content rating system across the world that can be used as a standard in developing a model of Malaysia digital game content rating system guideline. In order to achieve this objective, content analysis had been done by doing a comprehensive comparative analysis of ten existing content rating system across the world. As a result, it is found that there are fourteen different category of age classification that are 0+, 3+, 6+,7+, 10+, 12+, 13+, 14+, 15+, 16+, 17+, 18+, banned and others. The differences of age category implemented by these countries, show their emphasis in protecting specific target users.